2012 IEEE Colloquium on Humanities, Science and Engineering (CHUSER) 2012
DOI: 10.1109/chuser.2012.6504402
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of RFID technology for real-time materials tracking process in construction projects

Abstract: Abstract-The management of materials in construction projects is a key function that significantly contributes to the success of a project. Materials management is made problematic by materials shortages, delays in supply, price fluctuations, damage and wastage, and lack of storage space. Paper-based reports are mostly used to record and exchange information related to the materials component within a supply chain, which is problematic, error-prone, and inefficient. Generally, emerging technologies such as wir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…They further showed that with an automated information collection system, processes showed significant reductions in completion time. Apart from documenting the problem and its causes, there are several suggested solutions for an information collection system to maintain up-to-date information on inventory movement [17,18] using techniques and sensors similar to those used in warehousing and mass-manufacturing industries. To our knowledge, previous work addressing the problem of inventory tracking in the construction and shipbuilding industries focused on modes of information collection.…”
Section: Related Workmentioning
confidence: 99%
“…They further showed that with an automated information collection system, processes showed significant reductions in completion time. Apart from documenting the problem and its causes, there are several suggested solutions for an information collection system to maintain up-to-date information on inventory movement [17,18] using techniques and sensors similar to those used in warehousing and mass-manufacturing industries. To our knowledge, previous work addressing the problem of inventory tracking in the construction and shipbuilding industries focused on modes of information collection.…”
Section: Related Workmentioning
confidence: 99%
“…Meanwhile, among the factors affecting materials management effectiveness are unsystematic flow of materials, fluctuation of materials price, extensive multiple handling, improper sorting of materials, improper materials delivery, poor layout for materials handling, unavailability of up-todate inventory status, delay in materials delivery, excessive paperwork, equipment breakdown, shortage of equipment, poor coordination, inefficient communication, delay in procuring materials, errors in ordering, lack of materials storage, poor materials planning and so on [6,16,22,23]. Since these factors affect the material management process and are responsible for ineffective materials management, then, it is necessity to mitigate and addressed these factor in enhancing an effective materials management [1,10,24,25]. By addressing these, an effective materials management can be achieved.…”
Section: Influential Factors Of Effective Materials Managementmentioning
confidence: 99%
“…The management of a construction requires integrated processes to ensure that the work can be completed on time, cost and meet specified contract specifications [1]. This is because management that related to materials is very important from the design stage to the construction stage [2]. The management of building materials is generally recognized as an integrated coordination of material removal, purchase, delivery, receiving of materials on site, warehousing or storage and installation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a good planning and control system ensures the quality and quantity of a E3S Web of Conferences 65, 03005 (2018) https://doi.org/10.1051/e3sconf/20186503005 ICCEE 2018 building material is accurate and timely [6]. Good management is carried out to resolve potential problems such as material shortages, materials supply delays, non-schedule, material damage and wastage and lack of storage space [2]. While the issues often raised are related to congested site moreover in limited urban areas and site plans are reserved.…”
Section: Introductionmentioning
confidence: 99%